Immersive Narrative and Theatre Drama: A Cultural Planning Approach to Cultural Education - Chang, Yining (International Journal of Social Sciences and Public Administration, 2026)
Immersive narratives have been recognized as an independent form of participation in theatre drama for some time now; therefore, its impact on cultural dissemination differs from other forms such as traditional theatrical performance or classroom teaching. Examine the ways in which an immersive narrative and theatre drama, intended to serve as deliberate cultural education channels within cultural planning systems. Based on Dewey’s concept of experiential learning, Boal’s Theatre of the Oppression, Schechner’s Environmental Theatres Theory and Cultural Planning Approach, along with data from UNESCO and the Themed Entertainment Association, this article analyses four aspects of immersive theatrical cultural education to propose an implementing system model. As shown in the results, immersively integrated into a systematic plan for cultural development, it has produced Forms of cultural understanding, social participation and multicultural competence other educational models are unable to form effectively.